2006
DOI: 10.1007/s00125-006-0352-y
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic overexpression of brain natriuretic peptide prevents the progression of diabetic nephropathy in mice

Abstract: Aims/hypothesis Brain natriuretic peptide (BNP) is a potent vasorelaxing and natriuretic peptide that is secreted from the heart and has cardioprotective properties. We have previously generated hypotensive transgenic mice (BNP-Tg mice) that overproduce BNP in the liver, which is released into the circulation. Using this animal model, we successfully demonstrated the amelioration of renal injury after renal ablation and in proliferative glomerulonephritis. Glomerular hyperfiltration is an early haemodynamic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 54 publications
(58 reference statements)
2
21
2
Order By: Relevance
“…23 We previously showed that chronic excess of BNP in mice prevents glomerular injury after subtotal nephrectomy, 24 and ameliorates proteinuria and histologic changes in immune-mediated renal injury 25 as well as in diabetic nephropathy. 26 In addition to exerting direct vasodilating and diuretic actions, natriuretic peptides act to antagonize the RAAS at multiple steps. 14,27,28 We postulate therefore that the beneficial effects of natriuretic peptides should be brought about, at least in part, by antagonizing local activation and/or action of the RAAS in the kidney.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…23 We previously showed that chronic excess of BNP in mice prevents glomerular injury after subtotal nephrectomy, 24 and ameliorates proteinuria and histologic changes in immune-mediated renal injury 25 as well as in diabetic nephropathy. 26 In addition to exerting direct vasodilating and diuretic actions, natriuretic peptides act to antagonize the RAAS at multiple steps. 14,27,28 We postulate therefore that the beneficial effects of natriuretic peptides should be brought about, at least in part, by antagonizing local activation and/or action of the RAAS in the kidney.…”
mentioning
confidence: 99%
“…14,27,28 We postulate therefore that the beneficial effects of natriuretic peptides should be brought about, at least in part, by antagonizing local activation and/or action of the RAAS in the kidney. [24][25][26] To explore the role of natriuretic peptide/GC-A signaling in aldosterone-induced renal injury, we investigated renal findings of mice deficient in GC-A, along with the challenge of aldosterone and a high-salt diet.…”
mentioning
confidence: 99%
“…ANP has been shown to play an important function in the inhibition of RAAS [44,45]. ANP and brain natriuretic peptide (BNP) have been reported to prevent cardiac fibrosis [44,46] and renal fibrosis [47][48][49], and to reduce infarct size in acute myocardial infarction [50]. We demonstrated that AT1R, ACE, and atrial natriuretic peptide receptor (NPR-A) mRNA expression were increased and peaked at days 14, 7, and 7, respectively.…”
Section: Scraping Modelmentioning
confidence: 84%
“…We demonstrated that endogenous ANP, which was activated shortly within 45 min after rapid ventricular pacing, may be important in the control of GFR and renal sodium excretion in experimental AHF. It is relevant to state that recent studies of chronic overexpression of BNP in a murine model of diabetic glomerulopathy resulted in a preservation of glomerular structure and function (28). As a therapeutic strategy for AHF, ANP administration or agents that potentiate the effect of ANP may have renal therapeutic potential in AHF.…”
Section: Discussionmentioning
confidence: 99%